2010
DOI: 10.1111/j.1365-2699.2009.02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical changes in the distributions of invasive and endemic marine invertebrates are contrary to global warming predictions: the effects of decadal climate oscillations

Abstract: Aim We tested whether a hybrid zone that has formed between an endemic and an invasive species of marine mussel has shifted poleward as expected under a general hypothesis of global warming or has responded instead to decadal climate oscillations.Location We sampled 15 locations on the coast of California, USA, that span the distributions of the two species of marine mussels and their hybrids.Methods Mussels were sampled in 2005-08 and analysed at three nuclear gene loci using methods identical to those used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…Blue mussels are physiologically quiescent during winter (Bayne 1976), and there are no major differences in the SFG of M. edulis and M. galloprovincialis at cold temperatures in other seasons that would explain the inability of M. galloprovincialis populations to persist where winter temperatures are below 9 °C (Fly and Hilbish 2013). This cold-water limitation has been noted previously for European M. galloprovincialis populations (Hilbish et al 2012), as well as populations on the west coast of the U.S. (Hilbish et al 2010). There are several hypotheses on the mechanism of this limitation that warrant further investigation, including tolerance to cold-shock and reproductive abilities.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Blue mussels are physiologically quiescent during winter (Bayne 1976), and there are no major differences in the SFG of M. edulis and M. galloprovincialis at cold temperatures in other seasons that would explain the inability of M. galloprovincialis populations to persist where winter temperatures are below 9 °C (Fly and Hilbish 2013). This cold-water limitation has been noted previously for European M. galloprovincialis populations (Hilbish et al 2012), as well as populations on the west coast of the U.S. (Hilbish et al 2010). There are several hypotheses on the mechanism of this limitation that warrant further investigation, including tolerance to cold-shock and reproductive abilities.…”
Section: Discussionmentioning
confidence: 88%
“…This suggests that M. galloprovincialis might not have the same capability to recover from cumulative cold damage as M. edulis. Another possibility is that the reproductive capabilities of M. galloprovincialis are impeded at temperatures below 9 °C (Hilbish et al 2010, Fly and Hilbish (2013). SFG data were not collected for winter (A).…”
Section: Discussionmentioning
confidence: 99%
“…5d). Temperatures on these coasts are largely dominated by decadal changes in circulation patterns such as the Pacific Decadal Oscillation and the El Niño/Southern Oscillation 33,34 , which frequently alternate between contrasting warm and cold phases. Large-scale temperature fluctuations are important drivers on the biogeographic patterns observed on the Eastern pacific coast 35 , and while several studies have reported population and poleward range shifts associated with episodes of abnormally high SST 36,37 , others show that during cold phases species distributions may be driven in equatorialwards 33 , or may not change at all 38 .…”
Section: Global Patternsmentioning
confidence: 99%
“…Although the range limits of these congeners are still in flux due to shorter climatic variations, e.g. the Pacific Decadal Oscillation, the main hybrid zone ranges roughly from Monterey Bay to San Francisco Bay, with small numbers of M. galloprovincialis hybrids found further north to Humboldt Bay (Braby and Somero, 2006a;Hilbish et al, 2010). Field surveys indicate that the distribution within the hybrid zone is determined by both temperature and salinity (Braby and Somero, 2006a;Schneider and Helmuth, 2007).…”
Section: Introductionmentioning
confidence: 99%